2009
DOI: 10.1016/j.neuro.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal phthalate exposure and performance on the Neonatal Behavioral Assessment Scale in a multiethnic birth cohort

Abstract: We investigated the relationship between prenatal maternal urinary concentrations of phthalate metabolites and neonatal behavior in their 295 children enrolled in a multiethnic birth cohort between 1998 and 2002 at the Mount Sinai School of Medicine in New York City. Trained examiners administered the Brazelton Neonatal Behavioral Assessment Scale (BNBAS) to children within 5 days of delivery. We measured metabolites of 7 phthalate esters in maternal urine that was collected between 25 and 40 weeks’ gestation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 54 publications
5
134
0
Order By: Relevance
“…35 Also, there are studies which suggest that exposure to phthalates is associated with ADHD and ADHD behaviours, specifically conduct problems and concentration or orientation. [36][37][38] In our study, we found serum BPA and MEHP levels were higher in the ADHD group when compared to healthy controls. The high level of BPA and MEHP in the ADHD group may be related to those dopamine hypotheses.…”
Section: ____________________________________________________________supporting
confidence: 53%
“…35 Also, there are studies which suggest that exposure to phthalates is associated with ADHD and ADHD behaviours, specifically conduct problems and concentration or orientation. [36][37][38] In our study, we found serum BPA and MEHP levels were higher in the ADHD group when compared to healthy controls. The high level of BPA and MEHP in the ADHD group may be related to those dopamine hypotheses.…”
Section: ____________________________________________________________supporting
confidence: 53%
“…Based on results presented above, there seems to be possible association between exposure to phthalates (DEHP, and BBzP ) and the occurrence of asthma symptoms and allergy. The PCV flooring at home and the plastic wall urine [8,14,15,18,43,[49][50][51][52][53][54][57][58][59][60][61]64,73]. As phthalates are metabolized to their monoesters within a few hours or days [79,80], urinary phthalate monoesters are considered good biomarkers for assessing phthalate exposure in humans [8,62,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to overcome some of the major limitations of studies by choosing a longitudinal design with a follow-up of intraindividual changes. Such prospective design was used in some of the presented studies [8,18,38,43,57,[60][61][62]64,78]. Three studies used also casecontrol design [23,70,72].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations